The Politics of Unity in Malaysia: A Case Study of the 15th Malaysian General Election 2022 - Achmad Zahir Budiman; Hamka Hendra Noer (Eduvest - Journal of Universal Studies, 2025)
The 15th Malaysian General Election in 2022 is a democratic celebration in Malaysia which is held every five years. What was interesting about the 15th General Election was the political drama, because there were no political parties or coalitions that achieved a minimum majority, namely 122 seats out of 222 seats. Barisan Nasional and UMNO conducted a Unity Kingdom with Pakatan Harapan after the 15th General Election. In this research, researchers looked at qualitative methods for this case. Unity Politics is considered to be a new political constellation in Malaysia. This is because UMNO and Barisan Nasional have more experience than the other competing parties. Therefore, this research looks at how Pakatan Harapan was able to win in the 15th General Election and the joining of Barisan Nasional-UMNO to Pakatan Harapan.